ANALISIS PENGARUH KARAKTERISTIK INDIVIDU TERHADAP MOTIVASI (STUDI PADA PEGAWAI POLITEKNIK ILMU PELAYARAN SEMARANG) - Janny Adriani Djari (Politeknik Ilmu Pelayaran Semarang, 2018)
This research aim to to know individual characteristic influence to motivation ofPoliteknik Ilmu Pelayaran Semarang. Research regarding do individual characteristic influence intervening motivation andwork characteristic to labour capacity take population officer of Politeknik Ilmu PelayaranSemarang amounting to 218 people. Intake of sample with sampling random techniquerepresenting technique intake of sample at random with determination of is amount of sampelused by slovin formula obtained by 142 responder. As for data obtained with kuesioner withdata analysis use linear regression. Pursuant to research which have been done by hence can be obtained by the followingconclusion is existence of positive influence and signifikan between individual characteristicto motivation.